2016
DOI: 10.1155/2016/4847296
|View full text |Cite
|
Sign up to set email alerts
|

Low Dosage of Chitosan Supplementation Improves Intestinal Permeability and Impairs Barrier Function in Mice

Abstract: The purpose of this study was to explore relationships between low dose dietary supplementation with chitosan (COS) and body weight, feed intake, intestinal barrier function, and permeability in mice. Twenty mice were randomly assigned to receive an unadulterated control diet (control group) or a dietary supplementation with 30 mg/kg dose of chitosan (COS group) for two weeks. Whilst no significant differences were found between the conditions for body weight or food and water intake, mice in the COS group had… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 21 publications
1
7
0
Order By: Relevance
“…Several studies have been suggested that the actual processes of antimicrobial activity could be occurred by changing the bacterial membrane permeability, cytoplasmic membrane barrier function or nutrient transport. In addition, the mechanism of antimicrobial activity mostly depends on MW, the degree of de-acetylation (DD), type of bacterium, pH, and the concentration of active compounds connected to chitosan and its derivatives (Jarmila and Eva, 2011; Guan et al, 2016).…”
Section: Antimicrobial Properties and Regulation Of Microbiotamentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have been suggested that the actual processes of antimicrobial activity could be occurred by changing the bacterial membrane permeability, cytoplasmic membrane barrier function or nutrient transport. In addition, the mechanism of antimicrobial activity mostly depends on MW, the degree of de-acetylation (DD), type of bacterium, pH, and the concentration of active compounds connected to chitosan and its derivatives (Jarmila and Eva, 2011; Guan et al, 2016).…”
Section: Antimicrobial Properties and Regulation Of Microbiotamentioning
confidence: 99%
“…Results showed that dietary COS increased stomach pH, IL-6 (duodenum, jejunum, and ileum), and secretory IgA (duodenum and ileum), and reduced villus height and villus height to crypt depth ratio in the ileum. Thus the outcomes suggest that supplemental COS at low dosage may lead to immunological and oxidative stress in the small intestine and damage the integrity of the intestinal barrier in weaned piglets (Xiong et al, 2015; Guan et al, 2016).…”
Section: Effects On Performance Digestion and Intestinal Structure Imentioning
confidence: 99%
“…A noticeable rise in the intestinal permeation rate possibly due to the encapsulation of chitosan-phospholipid complex which opens the compact junctions of cytoplasmic transmembrane proteins occludin, claudin-1, and ZO-1 of epithelium cells and supports CAE to transfer paracellular. [38] The Bioadhesive nature of chitosan contributes to an improvement in residence time and a prolonged rate of adsorption at a mucosal site due to ionic interaction among positively charged alkaline polysaccharides of chitosan and negative charge of sialic acid groups in the intestine. [39] Stability study…”
Section: In Vitro Intestinal Permeation Studymentioning
confidence: 99%
“…Besides, supplying ICR mice with a 30 mg/kg dose of chitosan supplements for two weeks did not affect growth performance but impaired intestinal barrier integrity manifested by increased serum D-lactate content and decreased jejunal diamine oxidase activity. Moreover, the gene expression of intestinal tight junction proteins that are indispensable to maintain tight junction stability and barrier function including occludin and ZO-1 was significantly reduced due to compromised intestinal barrier integrity [ 133 ].…”
Section: Biological Functions Of Cosmentioning
confidence: 99%